Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To solve the summation [tex]\(\sum_{j=10}^{15}(2j - 7)\)[/tex], we will evaluate the expression [tex]\(2j - 7\)[/tex] for each integer value of [tex]\(j\)[/tex] from 10 to 15 and then sum the results.
1. Substitute [tex]\( j = 10 \)[/tex] into [tex]\( 2j - 7 \)[/tex]:
[tex]\[ 2(10) - 7 = 20 - 7 = 13 \][/tex]
2. Substitute [tex]\( j = 11 \)[/tex] into [tex]\( 2j - 7 \)[/tex]:
[tex]\[ 2(11) - 7 = 22 - 7 = 15 \][/tex]
3. Substitute [tex]\( j = 12 \)[/tex] into [tex]\( 2j - 7 \)[/tex]:
[tex]\[ 2(12) - 7 = 24 - 7 = 17 \][/tex]
4. Substitute [tex]\( j = 13 \)[/tex] into [tex]\( 2j - 7 \)[/tex]:
[tex]\[ 2(13) - 7 = 26 - 7 = 19 \][/tex]
5. Substitute [tex]\( j = 14 \)[/tex] into [tex]\( 2j - 7 \)[/tex]:
[tex]\[ 2(14) - 7 = 28 - 7 = 21 \][/tex]
6. Substitute [tex]\( j = 15 \)[/tex] into [tex]\( 2j - 7 \)[/tex]:
[tex]\[ 2(15) - 7 = 30 - 7 = 23 \][/tex]
Next, we sum all these results:
[tex]\[ 13 + 15 + 17 + 19 + 21 + 23 \][/tex]
Adding these terms sequentially, we get:
[tex]\[ 13 + 15 = 28 \][/tex]
[tex]\[ 28 + 17 = 45 \][/tex]
[tex]\[ 45 + 19 = 64 \][/tex]
[tex]\[ 64 + 21 = 85 \][/tex]
[tex]\[ 85 + 23 = 108 \][/tex]
Thus, the value of the summation is:
[tex]\[ \sum_{j=10}^{15} (2j - 7) = 108 \][/tex]
1. Substitute [tex]\( j = 10 \)[/tex] into [tex]\( 2j - 7 \)[/tex]:
[tex]\[ 2(10) - 7 = 20 - 7 = 13 \][/tex]
2. Substitute [tex]\( j = 11 \)[/tex] into [tex]\( 2j - 7 \)[/tex]:
[tex]\[ 2(11) - 7 = 22 - 7 = 15 \][/tex]
3. Substitute [tex]\( j = 12 \)[/tex] into [tex]\( 2j - 7 \)[/tex]:
[tex]\[ 2(12) - 7 = 24 - 7 = 17 \][/tex]
4. Substitute [tex]\( j = 13 \)[/tex] into [tex]\( 2j - 7 \)[/tex]:
[tex]\[ 2(13) - 7 = 26 - 7 = 19 \][/tex]
5. Substitute [tex]\( j = 14 \)[/tex] into [tex]\( 2j - 7 \)[/tex]:
[tex]\[ 2(14) - 7 = 28 - 7 = 21 \][/tex]
6. Substitute [tex]\( j = 15 \)[/tex] into [tex]\( 2j - 7 \)[/tex]:
[tex]\[ 2(15) - 7 = 30 - 7 = 23 \][/tex]
Next, we sum all these results:
[tex]\[ 13 + 15 + 17 + 19 + 21 + 23 \][/tex]
Adding these terms sequentially, we get:
[tex]\[ 13 + 15 = 28 \][/tex]
[tex]\[ 28 + 17 = 45 \][/tex]
[tex]\[ 45 + 19 = 64 \][/tex]
[tex]\[ 64 + 21 = 85 \][/tex]
[tex]\[ 85 + 23 = 108 \][/tex]
Thus, the value of the summation is:
[tex]\[ \sum_{j=10}^{15} (2j - 7) = 108 \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.